2022
DOI: 10.3389/fonc.2022.987484
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A case of radioactive iodine-refractory thyroid cancer accompanying cervical lymph node metastasis treated with US-guided RFA combined with 125I seed implantation

Abstract: BackgroundLocal control of metastases is critical to improving the life quality of patients with radioactive iodine-refractory (RAIR) thyroid cancer accompanying regional lymph node metastasis.Case reportThe reported patient suffered from RAIR thyroid cancer accompanying poorly controlled cervical lymph node metastasis. The patient’s lesions were controlled through 125I seed implantation combined with ultrasound-guided radio-frequency ablation (US-guided RFA). Such a combination therapy has not been reported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…For challenging and severe cases, including those with lesions protruding from the skin or rupture, this method offers safe and reliable treatment with high clinical utility. Zhai et al [ 58 ] found that US-guided RFA combined with iodine-125 implantation could safely and effectively control local metastatic tumors, while also improving patients’ quality of life. These findings demonstrate the utility of palliative RFA in the management of recurrent and metastatic PTC.…”
Section: Rfa For Recurrent and Metastatic Ptcmentioning
confidence: 99%
“…For challenging and severe cases, including those with lesions protruding from the skin or rupture, this method offers safe and reliable treatment with high clinical utility. Zhai et al [ 58 ] found that US-guided RFA combined with iodine-125 implantation could safely and effectively control local metastatic tumors, while also improving patients’ quality of life. These findings demonstrate the utility of palliative RFA in the management of recurrent and metastatic PTC.…”
Section: Rfa For Recurrent and Metastatic Ptcmentioning
confidence: 99%